Keadilan Bagi Investor Dalam Penerapan Skema Gross Split Pada Bidang Usaha Hulu Minyak aan Gas Bumi di Indonesia - Saputra, Angga (Media Hukum Indonesia (MHI), 2025)
In the presence of problems in the PSC (production sharing contract) cost recovery contract system, the government designed a new scheme, the Gross Split PSC. the purpose of this paper is that the author knows how justice for investors in applying the gross split scheme in the upstream oil and gas business in Indonesia. This scheme is designed to improve the efficiency and effectiveness of oil and gas production sharing schemes. Where by implementing this scheme it is hoped that the contractor can invest more efficiently in Indonesia, and this scheme provides greater flexibility and challenges for the contractor. So that if a contractor can invest more efficiently in Indonesia, the benefits will also be greater. PSC gross split scheme with a model that has never existed in the world was created through Minister of Energy and Mineral Resources Regulation No. 8 of 2017 concerning Gross Split Production Sharing Contracts. Unlike cost recovery PSC, the split between the Government and the contractor on the split PSC is fixed at the outset. Gross revenue is shared directly between the Government and the contractor. This PSC is also very fair for the Government and contractors. Split contractors can increase, also decrease, according to the specificity of the oil and gas fields to be managed.